2011
DOI: 10.1152/ajplung.00158.2010
|View full text |Cite
|
Sign up to set email alerts
|

Linking lung function and inflammatory responses in ventilator-induced lung injury

Abstract: Despite decades of research, the mechanisms of ventilator-induced lung injury are poorly understood. We used strain-dependent responses to mechanical ventilation in mice to identify associations between mechanical and inflammatory responses in the lung. BALB/c, C57BL/6, and 129/Sv mice were ventilated using a protective [low tidal volume and moderate positive end-expiratory pressure (PEEP) and recruitment maneuvers] or injurious (high tidal volume and zero PEEP) ventilation strategy. Lung mechanics and lung vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…Previous studies have showed that hydrogen has a potential anti-inflammatory effect (Kajiya et al, 2009;Gharib et al, 2001). TNF-α, IL-1β and IL-6 are potent proinflammatory cytokines that play a role in the initiation and amplification of inflammatory responses during ALI (Cannizzaro et al, 2010). Inhibiting the overproduction of pro-inflammatory cytokines such as TNF-α, IL-1β and IL-6 promotes the lessening of pulmonary injury in CLP-induced ALI model (Bhatia and Moochhala, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed that hydrogen has a potential anti-inflammatory effect (Kajiya et al, 2009;Gharib et al, 2001). TNF-α, IL-1β and IL-6 are potent proinflammatory cytokines that play a role in the initiation and amplification of inflammatory responses during ALI (Cannizzaro et al, 2010). Inhibiting the overproduction of pro-inflammatory cytokines such as TNF-α, IL-1β and IL-6 promotes the lessening of pulmonary injury in CLP-induced ALI model (Bhatia and Moochhala, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…[29] Chiumello et al [30] have reported an increase in cytokine concentrations in a group ventilated with high VT and zero PEEP. It has been suggested that considerably high VT may produce a similar degree of alveolar overdistension to that observed regionally in acute respiratory distress syndrome patients receiving much lower VT. [31] Therefore, in our study, the elevation of IL-6, and perhaps of IL-8 and IL-1β, could have been driven by high VT. A mouse model of ventilator-induced lung injury has shown that high-VT ventilation without preceding lung injury up-regulates intrapulmonary cytokines TNF-α. [32] TNF-α appears to be involved in the pathogenesis of both ventilatorinduced lung injury and multiorgan dysfunction syndrome.…”
Section: Discussionmentioning
confidence: 58%
“…[11,31] Moreover, the RM in our study was applied for a much longer period than what has been normally Vol-2 Issue-1 SIFT DESK used in other published animal models to assess the effects of this ventilatory strategy more accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines such as IL-1β, IL-6, and TNF-α, detected in BALF, have been reported to be associated with the development of VALI [2,4,9]. Endotracheal instillation of anti-TNF-α antibody or lack of p55 TNF-α receptor signaling in mice has been reported to be associated with attenuation of VALI [16,39].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of VALI is complex, involving factors including barotrauma, volutrauma, atelectasis, and biotrauma [9][10][11]. Some studies on animal models of VALI have shown that MV induces the release of proinflammatory cytokines/chemokines in the lung tissue, followed by accumulation of innate inflammatory leukocytes, such as neutrophils and macrophages [6].…”
Section: Introductionmentioning
confidence: 99%